2002
DOI: 10.1038/sj.ejcn.1601305
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, phosphorus and magnesium balance: FM 85 fortification of human milk does not meet mineral needs of extremely low birthweight infants

Abstract: Objective: Extremely low birthweight ( < 1000 g) infants are growing rapidly and their nutritional requirements for calcium, phosphorus, magnesium are high. Design: Prospective, mineral balance. Setting: The study was carried out at the Department of Neonatology, Virchow-Hospital, Charité Berlin and the Department of Molecular Trace Element Research, Hahn-Meitner-Institute Berlin. Subjects: Nineteen infants < 1000 g birthweight were admitted, nine infants dropped out and 10 infants (birthweight 730 -995 g), fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
8
0
2
Order By: Relevance
“…Using a commercially available human milk fortifier, Schanler and Abrams [1] reported that net calcium retention was 104 AE 36 mg/ kg/d in premature infants, a value approximating the in utero accretion rate during the third trimester. These retention values are well above those achieved using earlier human milk fortifiers [16] and those more recently reported using a human milk fortifier not used in the United States [19]. That fortifier led to minimally positive calcium retention and therefore little if any benefit to the baby.…”
Section: Premature Infantssupporting
confidence: 51%
“…Using a commercially available human milk fortifier, Schanler and Abrams [1] reported that net calcium retention was 104 AE 36 mg/ kg/d in premature infants, a value approximating the in utero accretion rate during the third trimester. These retention values are well above those achieved using earlier human milk fortifiers [16] and those more recently reported using a human milk fortifier not used in the United States [19]. That fortifier led to minimally positive calcium retention and therefore little if any benefit to the baby.…”
Section: Premature Infantssupporting
confidence: 51%
“…In the case of calcium, their daily loss (through excretion in the urine, fecal and dermal) are estimated at 420 mg/day. Calcium is absorbed in the intestine not ever exceeding 30% of the total amount ingested [18]. For absorption, calcium must compete with other substances such as phytates and oxalates act by inhibiting its absorption.…”
Section: Calcium-phosphorus Balancementioning
confidence: 99%
“…Assume-se, atualmente, que a alimentação enteral dos recém-nascidos pré-termo deva ser iniciada o mais preco-cemente possível, com leite humano, preferencialmente de suas próprias mães, recomendando-se fórmula especial para prematuros se não houver disponibilidade de LH (9,21,22) . Contudo, quando se atinge o volume enteral total, o LH deve ser suplementado, a fim de fornecer adequado aporte de nutrientes (23,24) , pois mesmo o LH da própria mãe do prematuro não supre todas as suas necessidades e pode não proporcionar ganho ponderal adequado (7,9,24) .…”
Section: Discussionunclassified
“…Ao final do estudo, os níveis de fosfatase alcalina das crianças de ambos os grupos eram menores do que os iniciais, sendo os valores médios do Grupo B mais baixos do que os do Grupo A, indicando maior atividade osteoblástica nas crianças deste grupo, o que sugere maior remodelação óssea ou solubilização de hidroxiapatita devido à menor absorção de fósforo e cálcio da dieta A (LH+FM 85 ® ), lembrando-se que esta dieta oferece 25% mais cálcio e fósforo que a dieta B. Uma possível explicação para este achado seria a menor absorção desses minerais devido à menor solubilidade do aditivo então disponível e de seus sais de cálcio e fósforo, com consequente menor biodisponibilidade destes micronutrientes no LH+FM 85 ® em relação ao LH adicionado com fórmula para prematuros (3,4) . Deve-se ainda ressaltar que o aditivo FM 85 ® recebeu modificações em sua formulação em relação ao produto oferecido neste estudo, obviamente para aprimorá-lo, pois outros autores verificaram que sua adição ao LH não supria as necessidades de minerais de prematuros extremos (4,23,27) .…”
Section: Discussionunclassified